DIMENSI SERAT DAN KOMPOSISI KIMIA KAYU ALPOKAT - Yacob Ando (Jurnal Penelitian Hasil Hutan, 1988)
The  fiber  dimension   and  chemical composition of  Persea sp. are presented  in this report.  The analyses include determination   of the  fiber  dimension (length, diameter cell  wall thickness, and Runkel ratio), and chemical composition. (cellulose, lignin, pentosan, ash,   extractives, and solubility in one percent  sodium hydroxide  solution).The study  reveals that the average  fiber length is 1105.36 µ, diameter 19. 09 µ,  cell wall thickness  2,36 µ and Runkel ratio  0.37.  The  cellulose  content amounts to 45.46  percent,  lignin 23.71 per cent,  pentosan  19.67 percent and ash 1.27 percent.The  solubility  in cold  water ; was found to be  5.43  percent;  in hot  water  5.55  percent, in alcohol  benzene 1:2 ratio,  4.02  percent  and in one  per cent sodiumhydroxide  solution 11.36 percent.Based on the  fiber dimension and the chemical composition, it was found that Persea wood  is suitable for producing good  quality  paper.